Ecology of the non-native snail Sinotaia cf quadrata (Caenogastropoda: Viviparidae). A study in a lowland stream of South America with different water qualities - Ferreira, Ana Clara (2017)
Sinotaia quadrata is a snail native from Asia recorded for the first time in South America in 2009 in central Argentina. In 2015, this species was also found in a lowland stream with different water qualities. Our aims were to contribute to the knowledge of its population ecology and to compare the individuals from the two locations anatomically. Snails were searched at 6 sites, where physicochemical and hydraulic parameters were measured. Biological samples were also taken at two sites (S3 and S4) to study the population traits of S. cf quadrata (density, size structure, fecundity and sex ratio) and to assess the water quality through macroinvertebrates' biological indices (richness, diversity and IBPamp). Physicochemical and biological parameters allowed us classifying sites as "moderately polluted" (S3) and "heavily polluted" (S4). At S4, the population showed a lower density, larger individuals, higher fecundity and a scarce representation of young snails. The differences observed in the radula and mantle border of snails from the two geographical regions might be attributed to environmental differences. We conclude that this species is tolerant to a wide range of environmental variables which, along with its high fecundity and morphological plasticity, could allow this species to colonize neighbor streams.